Knowledge Through Digitalization: Innovation of IT Center & Lab in Rural Areas - Yadav, Mohit; Patel, Omprakash; Sharma, Anurag (International Journal of Computer Sciences and Engineering, 2025)
Today’s world is forwarding towards new technology to becoming smarter and advanced. Every person had a smartphone as well as laptop but some people, mainly in rural areas don’t know the actual use of a smartphone. They are only Accessing Social media. So the main purpose of this paper is to tell about that how the people from rural areas are aware by new technologies by the implementation of Information Technology centre and laboratory with different methodology. This Information Technology centre and laboratory change the set mind of the rural people. For this innovation, we want users and their innovation with experimentation and suitability of methodology created by us for the environment to reach to the goals.